PARSHA DISEASE OCCURRING IN THE FRUIT ORCHARDS OF SURXONDARYO REGION AND CONTROL MEASURES AGAINST IT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article provides information on the scientific research work on the disease Parsha, which causes serious damage to trees in the orchards of Surkhandarya region, and measures to combat it. This disease is a fungal disease, and as a result of this very common disease, the quality of the fruit is impaired and the exportability property is impaired.